2019
DOI: 10.1017/s1049023x19004254
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Cardiovascular Health Metrics in Emergency Medical Technicians Compared to Paramedics: A Cross-Sectional Study of Emergency Medical Services Professionals

Abstract: Background:Emergency Medical Services (EMS) professionals face high physical demands in high-stress settings; however, the prevalence of cardiovascular health (CVH) risk factors in this health care workforce has not been explored. The primary objective of this study was to compare the distribution of CVH and its individual components between a sample of emergency medical technicians (EMTs) and paramedics. The secondary objective was to identify associations between demographic and employment characteristics wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Those at the ALS certification level were slightly older (mean age 37.1 years) compared to those at the BLS level (mean age 32.8 years). As seen in past samples of this population (6,7,37), most respondents were men and non-Hispanic white, with some differences between ALS and BLS EMS personnel. There was a higher population proportion of men (78%) and non-Hispanic whites (86%) for ALS compared to BLS (67% men, 74% non-Hispanic white).…”
Section: Demographicsmentioning
confidence: 61%
See 3 more Smart Citations
“…Those at the ALS certification level were slightly older (mean age 37.1 years) compared to those at the BLS level (mean age 32.8 years). As seen in past samples of this population (6,7,37), most respondents were men and non-Hispanic white, with some differences between ALS and BLS EMS personnel. There was a higher population proportion of men (78%) and non-Hispanic whites (86%) for ALS compared to BLS (67% men, 74% non-Hispanic white).…”
Section: Demographicsmentioning
confidence: 61%
“…Descriptive statistics with appropriate survey weighting were calculated. Based on prior work demonstrating that some key health outcomes differ between demographic groups within EMS, prevalence estimates were compared across age groups, sex, and EMS certification levels (6,7). For all descriptive statistics, unweighted frequency and population-weighted proportion or weighted mean and standard error are presented.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has shown that EMS personnel have a high prevalence of poor health for certain LS7 components such as obesity, poor diet, and inadequate physical activity. 7 , 8 , 9 EMS personnel also have a high prevalence of non‐traditional CVD risk factors, such as poor sleep quality, short or long sleep duration, and high stress, 10 , 11 , 12 , 13 which may further increase the risk of developing CVD. No prior studies have examined the relationship between sleep, stress, and CVH within the occupational group of EMS personnel.…”
Section: Introductionmentioning
confidence: 99%